Amyloid β accumulation and inner retinal degenerative changes in Alzheimer's disease transgenic mouse. (3rd June 2016) - Gupta, Vivek K.; Chitranshi, Nitin; Gupta, Veer B.; Golzan, Mojtaba; Dheer, Yogita; Wall, Roshana Vander; Georgevsky, Dana; King, Anna E.; Vickers, James C.; Chung, Roger; Graham, Stuart
Highlights: Increased Amyloid β accumulation was observed in retina. A loss of scotopic threshold response amplitudes was demonstrated in AD mice. Slight elevation of intraocular pressure was detected. Retinal thinning particularly related to inner retina was identified. Abstract: The APP-PS1ΔE9 mouse model of Alzheimer's disease (AD) exhibits age dependent amyloid β (Aβ) plaque formation in their central nervous system due to high expression of mutated human APP and PSEN1 transgenes. Here we evaluated Aβ deposition and changes in soluble Aβ accumulation in the retinas of aged APP-PS1 mice using a combination of immunofluorescence, retinal flat mounts and western blotting techniques. Aβ accumulation in the retina has previously been shown to be associated with retinal ganglion cell apoptosis in animal models of glaucoma. This study investigated changes in the inner retinal function and structure in APP-PS1 mice using electrophysiology and histological approaches respectively. We report for the first time a significant decline in scotopic threshold response (STR) amplitudes which represents inner retinal function in transgenic animals compared to the wild type counterparts (p < 0.0001). Thinning of the retina particularly involving inner retinal layers and reduction in axonal density in the optic nerve was also observed. TUNEL staining was performed to examine neuronal apoptosis in the inner retina. Intraocular pressure (IOP) measurements showed that APP-PS1ΔE9 mice had a slightly elevated IOP, but the significance of this finding is not yet known. Together, these results substantiate previous observations and highlight that APP-PS1ΔE9 mice show evidence of molecular, functional and morphological degenerative changes in the inner retina.